Clinical profile and serum homocysteine level in young patients with stroke: a prospective, observational study - S., Manoharan; K., Sathyasagar; M., Natesh Prabhu (International Journal of Advances in Medicine, 2019)
Background: According to the WHO, stroke is the second most important cause of death in elderly people with age >60 years and fifth leading cause in the age group of 15 to 59 years. Hyperhomocysteinemia has been linked to increased incidence of ischemic strokes. Thus, the aim of the present study was to assess serum homocysteine levels as an individual risk factor of stroke in young patients. Methods: This was a prospective, cross-sectional, single center study performed in 50 patients admitted in the Department of Medicine, Thanjavur Medical College and Hospital, Thanjavur, over a period of 7 months (i.e., from December 2013 to June 2014). Young patients, aged 1545 years, and diagnosed with stroke were included in the study. Serum homocysteine was measured by fluorescein polarization immunoassay (FPIA). Significant difference between the patients with normal and elevated mean serum homocysteine levels was identified by using unpaired t-test. P value ≤0.05 was considered as statistically significant. Results: Majority of the stroke patients were male (78%). Similarly, male patients dominated the total number of patients with elevated serum homocysteine levels (75%). Thirty-two (64%) patients had an elevated serum homocysteine level. There was a significant difference between the patients with increased homocysteine levels as compared to patients with normal homocysteine levels (p value <0.05). Out of 32 patients with hyperhomocysteinemia, 27 (84.38%) patients had ischemic stroke, 4 (12.50%) had cortical vein thrombosis and 1 (3.12%) had hemorrhagic stroke. Conclusions: Findings of the present study confirm that hyperhomocysteinemia is associated with an increased incidence of stroke in young patients. As healthcare providers, we must stress on prevention of stroke, especially by identifying treatable risk factors.